Grace in Resistance: Karnataka’s Female Classical Dancers and the Freedom Movement - Seema S. Upadhyaya (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This paper explores the overlooked yet influential role of Karnataka’s female classical dancers in India’s freedom struggle, focusing on two key figures K. Venkatalakshamma and Shanta Rao. It situates their artistic practice within the socio-political and cultural contexts of colonial Mysore, demonstrating how dance served as both a spiritual discipline and a subtle form of political expression. Drawing upon archival sources, biographies, oral histories, and performance theory, the study reveals how these women transformed ritual and court traditions condemned by colonial morality into acts of aesthetic resistance. Their performances carried nationalist themes through mythic allegory, devotional emotion, and artistic precision, allowing political ideas to resonate in veiled yet powerful forms. Through pedagogy and institutional engagement, they secured continuity for classical dance within modern education and post-independence cultural policy. The paper also interrogates gendered aspects of cultural nationalism, showing how women dancers negotiated respectability and agency through art. Ultimately, Karnataka’s female artists contributed to India’s cultural sovereignty, embodying a “grace in resistance” that merged artistic devotion with the moral imagination of freedom.